A 2D pixel detector for very high-rate X- and gamma-ray spectroscopy and imaging. Issue 2 (3rd May 2017) - Nygård, Einar; Malakhov, Nail; Weilhammer, Peter; Dorholt, Ole; Røhne, Ole M.; Nagano, Terumasa; Yamamoto, Koei
Abstract : A new methodology for very high-speed, energy-dispersive detection of X-ray fluorescence is being developed. The underlying reasoning behind it, as well as early results from the evaluation of the first prototype, is presented.